Outcomes of systemic therapy for advanced triple-negative breast cancer: A single centre experience. (August 2018) - Battisti, Nicolò Matteo Luca; Okonji, David; Manickavasagar, Thubeena; Mohammed, Kabir; Allen, Mark; Ring, Alistair
Abstract: Background: Prognosis is worse for advanced triple-negative breast cancer (aTNBC) compared to other disease subtypes. Trials describe treatment outcomes in single specified lines of therapy; but few data describe treatment outcomes across the whole treatment pathway, which is critical in determining when patients should be referred for trials and to inform discussion. We evaluated treatment outcomes for aTNBC (overall response rate [ORR], median progression-free survival [mPFS] and median overall survival [mOS]) in patients treated largely outside of clinical trials. Methods: We retrospectively identified 268 patients diagnosed with aTNBC from 01/12/2011 to 30/11/2016 from our electronic records and recorded patients' and tumour characteristics and treatment outcomes. Chi-squared/Fishers exact test and Kaplan-Meier statistical methods were utilised. Results: 186 patients treated with ≥1 line of systemic treatment were eligible and had median age of 55 (range 26–91). 53.8% had ECOG Performance Status 0 and 69.9% visceral involvement. 38.6% had disease-free interval (DFI)≤12 months following surgery or adjuvant chemotherapy completion and 14.0% had de-novo advanced disease. 11.4% carried a BRCA mutation. 64.5% received two lines of therapy, 37.6% three and 21.5% four. ORR and mPFS were 43.9% and 3.7 months for first-line therapy, 40.2% and 3.5 months for second-line, 28.8% and 2.5 months for third-line and 25.0% and 2.1 months for fourth-line. In first line, DFI>12 months was associated with higher ORR and longer PFS compared DFI ≤12 months. Conclusions: The observed response rates are consistent with literature. However, PFS is short, and early consideration of clinical trials can be justified in these patients. Highlights: Response rates to standard systemic therapy are consistent with previous findings. Progression-free and overall survival are short in our real-world experience. Only disease-free interval and performance status predict outcomes. Clinical trials should be considered early in this population.